Routine Immunization Uptake and Knowledge of Caregivers in Selected Rural Communities in Northwestern Nigeria - Ameen, Hafsat; Musa, Shehu; Ibraheem, Rasheedat; Oladiji, Femi; Musa, Omotosho; Salaudeen, Adekunle (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Childhood immunization remains a public health problem in Nigeria, as the status did not improve substantially during the last two decades, especially in northern Nigeria. Understanding the level of routine immunization uptake of children among caregivers is important if a healthy community is to be maintained.Aim: This study aimed to investigate the knowledge and level of routine immunization uptake among caregivers in Bukkuyum Local Government of Zamfara State, Nigeria.Settings and Design: A descriptive cross-sectional study involving 320 caregivers selected using a multistage sampling technique was conducted.Materials and Methods: Sociodemographics, vaccination details, and knowledge were obtained via a semi-structured interviewer-administered questionnaire.Statistical Analysis Used: Data collected was analyzed using Statistical Package for Social Sciences (SPSS) statistics for Windows, version 21.0.Results:Findings show abysmally low levels of uptake of routine immunization antigens, namely, Bacille Calmette- Guerine (BCG) (26.1%), Oral Polio Vaccine LGAs= Local Government Areas (OPV) (42.5%), pentavalent vaccine (18.9%), and measles (13.0%). Only 80 (25.0%) children were fully immunized, 93 (29.0%) partially immunized, and 147 (46.0%) nonimmunized. Most respondents had poor knowledge (308 (96.2%)) and poor attitudinal disposition (173 (54.1%)) toward routine immunization.Conclusion: The vaccination uptake and knowledge of immunization among caregivers in the study area are poor. Caregivers' continual health education and a step-up of mobile health education activities by healthcare providers are crucial to improve routine immunization uptake in the study area.
Keywords: Caregivers’ knowledge; Northwestern Nigeria; routine immunization; vaccine uptake